Community activity pavilion and public swim complex [copy transparency] - Palm Springs Collaborative::::::::: (1970)
Rendering of community pool. Drawing is attributed to the Palm Springs Collaborative, whose members include John J. Cody, Donald A. Wexler, and Patrick Sheehy. The drawing lists William F. Cody as the City Architect.